Hyperreality Phenomenon in Virtual Roleplay Games (Case Study on The Seasons Group) - Alwan, Sheryl; Pienrasmi, Hanindyalaila; Poyo, Denu (Interaction Communication Studies Journal, 2025)
The development of digital technology today has brought forth various new forms of entertainment that not only function as a means of relaxation, but also create alternative social spaces for their users. One form of digital entertainment that has become increasingly popular among young people is virtual roleplay. This activity involves roleplaying in a digital environment designed to closely resemble everyday reality, whether in terms of appearance, interaction, or social dynamics. The phenomenon of roleplay becomes even more intriguing because player involvement is not limited to entertainment alone, but also extends to the formation of identity, social relations, and even influences emotional life in the real world. This indicates that virtual spaces no longer merely serve as reflections of reality, but have transformed into alternative worlds that significantly shape how individuals perceive themselves and others. Based on this background, this study aims to examine the phenomenon of hyperreality experienced by members of the roleplay group The Seasons. Jean Baudrillard’s theory of simulacra and hyperreality is employed as the main analytical framework to explain how digital representations can transform into realities that are perceived as more authentic and meaningful than reality itself. To achieve this objective, a qualitative approach was applied with data collected through semi-structured interviews conducted both online and offline, direct observation of player activities, and documentation related to their interactions within the roleplay world as well as outside the game. The research subjects consist of group administrators as key informants, group members who are actively involved and exhibit signs of hyperreality as primary informants, and family or friends in the real world who serve as supporting informants. The collected data was analyzed through the stages of data reduction, data presentation, and conclusion drawing in order to obtain an in-depth understanding of the phenomenon under study. The findings indicate that the roleplay world within The Seasons group has reached the stage of the Third Order of Simulacra as explained by Jean Baudrillard. At this stage, representations no longer refer to real-world reality, but instead create a new reality that is fully lived by the players. The conclusion of this study emphasizes that roleplay is not merely a digital game, but has evolved into a genuine social space in which hyperreality fully operates in shaping identity construction, communication, and interpersonal relations. Thus, this research contributes academically to the understanding of digital simulation phenomena and enriches the study of the relevance of Baudrillard’s theory of simulacra and hyperreality to contemporary digital cultural practices.